Increased hormetic dose of glyphosate causes oxidative stress and reduces yield in common bean - Pacheco de Almeida Prado Bortolheiro, Fernanda [UNESP]; Brunelli-Nascentes, Marcela Cristina [UNESP]; Luiz Santos, Hariane [UNESP]; de Almeida Silva, Marcelo [UNESP] (Elsevier, 2023)
Glyphosate can alter several physiological and biochemical processes and even plant nutrient absorption. This study aimed to verify whether biochemical and non-biochemical variables of the antioxidant complex are affected by low doses, considered hormetic, of glyphosate herbicide. Two experiments were conducted in the field, one in the winter and the other in the wet season, with the early cycle common bean cultivar IAC Imperador. The experimental design was in a randomized block, consisting of applying low doses of glyphosate (0.0, 1.8, 7.2, 12, 36, 54, and 108 g a.e. ha–1) in the phenological stage V4, with four replicates. Environmental conditions, such as air temperature, interfered in the early cycle common bean response to low doses of glyphosate. Lower doses of glyphosate did not alter the gas exchange of bean plants. However, the increase in the glyphosate doses reduced the net CO2 assimilation rate, stomatal conductance, and transpiration rate while increasing the SOD and CAT activity, and MDA and proline content. In the winter season, the dose 7.2 g a.e. ha–1 increased bean productivity, while the dose 36 g a.e. ha–1 induced oxidative stress in bean plants and reduced productivity. In the wet season, doses 36 and 54 g a.e. ha–1 increased bean productivity, and the dose 108 g a.e. ha–1 decreased grain yield. Thus, the more favorable climatic conditions in the wet season enhance plant metabolism, subsequently increasing plant tolerance to higher glyphosate doses.
Keywords: Antioxidant enzymes; Bean productivity; Hormesis; N-(phosphonomethyl)glycine; Phaseolus vulgaris L.